Lifestyle risk factor related disparities in oral cancer examination in the U.S: a population-based cross-sectional study - Aderonke A. Akinkugbe; Dina T. Garcia; Tegwyn H. Brickhouse; Maghboeba Mosavel (BMC, 2020)
Abstract Background Oral cancers account for 3% of annual U.S. cancer diagnosis, 2 in 5 of which are diagnosed late when prognosis is poor. The purpose of this study was to report the population-level prevalence of oral cancer examination among adult smokers and alcohol drinkers and assess if these modifiable lifestyle factors are associated with receiving an oral cancer examination. Methods Adult participants ≥30 years (n = 9374) of the 2013-2016 cycles of the National Health and Nutrition Examination Survey were included. Oral cancer examination (yes/no), smoking (never, former, current) and alcohol use (abstainers, former, current) were self-reported. Survey-logistic regression estimated odds ratios (OR) and 95% confidence intervals (CIs) of ever and past year oral cancer examination adjusted for age, gender, race/ethnicity, education, income, and time since last dental visit. Results One third (33%) reported ever been examined for oral cancer, 66% of whom reported an examination in the past year. Adjusted OR (95% CI) of past year examination comparing current and former smokers to non-smokers were 0.51 (0.29, 0.88) and 0.74 (0.53, 1.04) respectively. Similarly, current and former alcohol drinkers relative to abstainers were less likely to report a past year oral cancer examination, OR (95% CI) = 0.84 (0.53, 1.30) and 0.50 (0.30, 0.83) respectively. Conclusion This study showed that smokers and alcohol users were less likely than abstainers to self-report a past year oral cancer examination. Access to affordable and targeted oral cancer examination within the dental care setting might ensure that these high-risk individuals get timely examinations and earlier diagnosis that might improve prognosis and survival.